Anastomosing hemangioma of the ovary mimics metastatic ovarian cancer - Andrew Rezk; Stephanie Richards; R. Patricia Castillo; Matthew Schlumbrecht (Elsevier, 2020)
Anastomosing hemangioma (AH) is an uncommon benign vascular tumor reported to occur in the kidney and, in rare instances, the ovary. While most cases of AH in the ovary are incidental findings, we report a case of ovarian AH presenting with abdominal ascites and elevated CA-125 suggestive of metastatic ovarian cancer. Postoperative histopathologic examination demonstrated a tumor consisting of numerous vascular spaces lined by benign-appearing endothelial cells with exuberant hilus cell hyperplasia. These characteristics led to the diagnosis of anastomosing hemangioma of the ovary. A summary of the characteristics of AH, along with a review of all previously reported cases and possible theories for its presentation, are discussed.